KARAKTERISTIK SURIMI DARI CAMPURAN DAGING MANYUNG DAN CUCUT - Iwan Yusuf Bambang Lelana; Amir Husni (Universitas Gadjah Mada, 2008)
Manyung (Arius spp.) and shark (Carcharhinus sp.) are the most of low value fishes in Yogya. In order to increase the value, the fishes were processed into surimi. In this research, fishes were mixed in different ratio of manyung and shark, namely 90%:10%, 70%:30%, 50%:50%, 30%:70%, and 10%:90%. The water content, protein content, lipid content, sensory properties and gel strength were determined. The result showed that surimi from manyung and shark in ratio of 90%:10% produced the highest folding test value (AA) and the highest score of sensory properties.